„Antibiotic-stewardship“(ABS)-Strategien in der urologischen Praxis und Klinik - Lichtinger, U. (Urologe A, 2020)
Antibiotics are effective and safe drugs which have saved millions of lives since their inception. The World Health organization (WHO) has identified increasing antibiotic resistance worldwide as one of the greatest health problems of our time. The most common indications for antibiotic therapy include urinary tract infections, but according to current data, a very high percentage of these are not treated in accordance with guidelines. To prevent the continuous selection of resistant bacteria, and undesirable or even dangerous side effects such as by avoiding damage to the patient’s microbiome, strategies through antibiotic stewardship (ABS) are urgently needed. Especially for urologists in outpatient care, this requires new, innovative and sustainable training concepts that keep knowledge continuously up-to-date and support appropriate antibiotic prescriptions.